2011
DOI: 10.1164/rccm.201001-0051oc
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea in Patients with Abdominal Aortic Aneurysms

Abstract: In patients with AAA, OSA is highly prevalent. Severe OSA may be a causal factor for faster AAA expansion, but this needs to be proved in a randomized controlled intervention trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
52
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 32 publications
6
52
1
1
Order By: Relevance
“…An international multicentre study found that ∼40% of patients aged 18-75 years in an AAA surveillance register presented with an AHI >10 events·h −1 [59]. Cross-sectional data indicated no association of aortic diameter with AHI [59].…”
Section: −1mentioning
confidence: 99%
See 3 more Smart Citations
“…An international multicentre study found that ∼40% of patients aged 18-75 years in an AAA surveillance register presented with an AHI >10 events·h −1 [59]. Cross-sectional data indicated no association of aortic diameter with AHI [59].…”
Section: −1mentioning
confidence: 99%
“…Cross-sectional data indicated no association of aortic diameter with AHI [59]. In order to investigate a possible association between OSA/AHI and rate of AAA expansion, MASON et al [59] assessed patients with AAA during a median follow-up interval of 18 months.…”
Section: −1mentioning
confidence: 99%
See 2 more Smart Citations
“…Khayi et al, suggest that the regulation of ocular blood flow, which partially depends on the sympathetic and parasympathetic systems, is not altered without comorbidities associated with OSAHS (25) . However, it has been shown that there is an increased risk of cardiovascular and pulmonary diseases in OSAHS patients (29) . An increased risk of glaucoma in OSAHS patients may also be associated with additional pathologies that are compatible with the vascular theory of glaucoma.…”
Section: Discussionmentioning
confidence: 99%